2019
DOI: 10.1126/sciadv.aax9140
|View full text |Cite
|
Sign up to set email alerts
|

Current status of opioid addiction treatment and related preclinical research

Abstract: Opioid use disorders (OUDs) are diseases of the brain with behavioral, psychological, neurobiological, and medical manifestations. Vulnerability to OUDs can be affected by factors such as genetic background, environment, stress, and prolonged exposure to μ-opioid agonists for analgesia. Two standard-of-care maintenance medications, methadone and buprenorphine-naloxone, have a long-term positive influence on health of persons with opioid addiction. Buprenorphine and another medication, naltrexone, have also bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 106 publications
2
40
0
5
Order By: Relevance
“…Moreover, variations in who receives OAT and time to enter treatment based on sociodemographic and institutional characteristics highlight further areas for further study and potential intervention. In addition, further research is needed regarding personalised approaches to characterising the inheritable factors which contribute towards heightened risk of OUD as well as potential avenues for more effective treatment [40]. Nevertheless, given the limitations of the TEDS-A dataset, we are unable to unravel the causal mechanisms which underlie these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, variations in who receives OAT and time to enter treatment based on sociodemographic and institutional characteristics highlight further areas for further study and potential intervention. In addition, further research is needed regarding personalised approaches to characterising the inheritable factors which contribute towards heightened risk of OUD as well as potential avenues for more effective treatment [40]. Nevertheless, given the limitations of the TEDS-A dataset, we are unable to unravel the causal mechanisms which underlie these differences.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most widely used effective treatments for opioid addiction ( Kreek et al, 2019 ) involves the prolonged prescription of methadone as an alternative to the abused opioid. Methadone is a synthetic opioid with a different chemical structure compared with other clinically prescribed opioids (e.g., morphine, oxycodone, fentanyl, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…A MOR agonist like morphine and heroin, methadone has less abuse potential than these classic opioid drugs ( Kreek, 2000 ) and is an effective antinociceptive agent in patients with pain that do not respond to other analgesics ( Weschules and Bain, 2008 ). Although approximately 20%–40% of individuals drop out of methadone maintenance treatment ( Kreek et al, 2019 ), this treatment still has greater retention than buprenorphine maintenance, making one wonder what makes methadone so special.…”
Section: Introductionmentioning
confidence: 99%
“…Several genetic studies (primarily case-control studies) have been carried to determine the impact A118G variant both on the onset and treatment of opioid and other addictions. Outcomes are highly diverse in which some studies have shown a significant association of A118G with opioid addiction while other studies have failed to obtain such evidence 41. The probability to develop opioid addiction is less in Hispanic 118G carriers compared to individuals with African-American or Caucasian ethnic backgrounds 11.…”
Section: Medication Strategies For Opioid Addictionmentioning
confidence: 99%